Advanced glycation end-products (AGEs) induce concerted changes in the osteoblastic expression of their receptor RAGE and in the activation of extracellular signal-regulated kinases (ERK) - Cortizo, Ana María (2003)
An increase in the interaction between advanced glycation end-products (AGEs) and their receptor RAGE is believed to contribute to the pathogenesis of chronic complications of Diabetes mellitus, which can include bone alterations such as osteopenia. We have recently found that extracellular AGEs can directly regulate the growth and development of rat osteosarcoma UMR106 cells, and of mouse calvaria-derived MC3T3E1 osteoblasts throughout their successive developmental stages (proliferation, differentiation and mineralisation), possibly by the recognition of AGEs moieties by specific osteoblastic receptors which are present in both cell lines. In the present study we examined the possible expression of RAGE by UMR106 and MC3T3E1 osteoblastic cells, by immunoblot analysis. We also investigated whether short-, medium- or long-term exposure of osteoblasts to extracellular AGEs, could modify their affinity constant and maximal binding for AGEs (by 125I-AGE-BSA binding experiments), their expression of RAGE (by immunoblot analysis) and the activation status of the osteoblastic ERK 1/2 signal transduction mechanism (by immunoblot analysis for ERK and P-ERK). Our results show that both osteoblastic cell lines express readily detectable levels of RAGE. Short-term exposure of phenotypically mature osteoblastic UMR106 cells to AGEs decrease the cellular density of AGE-binding sites while increasing the affinity of these sites for AGEs. This culture condition also dose-dependently increased the expression of RAGE and the activation of ERK. In proliferating MC3T3E1 pre-osteoblasts, 24-72 h exposure to AGEs did not modify expression of RAGE, ERK activation or the cellular density of AGE-binding sites. However, it did change the affinity of these binding sites forAGEs, with both higher- and lower-affinity sites now being apparent. Medium-term ( 1 week) incubation of differentiated MC3T3E1 osteoblasts with AGEs, induced a simultaneous increase in RAGE expression and in the relative amount of P-ERK. Mineralising MC3T3E1 cultures grown for 3 weeks in the presence of extracellular AGEs showed a decrease both in RAGE and P-ERK expression. These results indicate that, in phenotypically mature osteoblastic cells, changes in ERK activation closely follow the AGEs-induced regulation of RAGE expression. Thus, the AGEs-induced biological effects that we have observed previously in osteoblasts, could be mediated by RAGE in the later stages of development, and mediated by other AGE receptors in the earlier pre-osteoblastic stage.